The Edinburgh companion to literature and music - Sousa Correa, Delia da (Edinburgh University Press, 2020)
This trailblazing companion charts and extends the work in this expanding interdisciplinary field and is an essential resource for researchers with an interest in literature and other media.
Keywords: Music and literature.; Literature -- History and criticism.; Musique et littérature.; Littérature -- Histoire et critique.; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Literature; Music and literature; Criticism, interpretation, etc.